Strategi Pengembangan Oukup Sebagai Ekowisata Kesehatan Kabupaten Karo - Batubara, Rima Pratiwi (Jurnal Ilmiah Pariwisata, 2020)
Oukup is an effort to restore and/or look for healthy condition by means of a steam bath using traditional spices. Problems related to business licensing, adequate theraphy to diverge to a decrease in community participation in maintaining sustainable. Observation were carried out in Berastagi, Karo, North Sumatera. The research is descriptive with exploratory survey approach. Data were analyzed by SWOT Analysis. The results of the analysis obtained a value of 1,05 (IFAS) and 0,90 (EFAS) are in Quadrant 1. Aggressive strategy is done by registering enough data to provide health tourism amenities.